Development of processing technologies for gluten-free and plant-based food applications - Pulivarthi, Manoj Kumar (My University, 2025)
The increasing demand for gluten-free and plant-based products has driven the need for high-quality alternative ingredients that offer both functionality and sustainability. Sorghum and pulses like yellow peas and red lentils are promising sources, requiring advanced processing techniques to optimize their use in diverse food applications. This thesis investigates milling and protein fractionation processes to enhance the functionality and application potential of sorghum- and pulse-based flours and protein fractions. A detailed review of current research on dry fractionation for producing functional, protein-rich ingredients highlights its sustainable and eco-friendly advantages as an alternative to intensive wet fractionation. In Chapter 3, a roller milling technique combined with ultrasound tempering (UST) was developed to produce high-quality white and sumac sorghum flours for gluten-free applications. UST significantly impacted milling yield, particle size, starch damage, and ash content. Notably, the milling yield of white sorghum increased from 73.3% (control) to 76.6–78.2% with treatment durations. A 1-minute UST enabled efficient bran separation, lowering ash content to 0.87% in white sorghum and 0.69% in red-tannin sorghum, compared to 1.05% and 1.4% in controls. This optimized milling approach proved suitable for both sorghum varieties, enhancing flour quality regardless of physical property differences. Chapter 4 examined the rheological properties and baking performance of UST-treated white and sumac sorghum flours. Mixolab and rapid visco analyzer (RVA) results demonstrated enhanced starch gelatinization and retrogradation, particularly in sumac sorghum. UST improved bread quality by reducing hardness and enhancing crumb structure, with the most notable improvements in sumac sorghum. While cookie quality was unaffected by UST time, both sorghum flours showed good cookie baking performance. In Chapter 5, roller milling settings were optimized to produce dehulled yellow pea and red lentil flours of various particle sizes (small, medium, and large) with minimal nutritional differences. The geometric mean diameters for red lentil flours were 56.05 μm (small), 67.01 μm (medium), and 97.17 μm (large), while yellow pea flours ranged from 41.38 μm to 98.31 μm. Starch damage increased with smaller particle sizes due to intensified milling, impacting flowability and suggesting roller milling as an effective technique for producing flours with varied functional applications. The final study compared dry and wet fractionation methods for producing protein-rich red lentil fractions. Air classification, a dry fractionation method, achieved up to 60.53% protein content with a recovery of 19.52%. Optimal protein purity and yield (57.84% protein at 6,000 rpm with 29.96% recovery) were achieved with a 22 μm cut point. Wet fractionation produced protein isolates with up to 89.23% protein content, while the mild-alkaline red lentil concentrate reached 64.24%. Functional testing showed the wet-extracted isolate excelled in emulsifying capacity (EC), water absorption (WAC), and oil absorption (OAC), while dry-fractionated proteins offered enhanced foaming, solubility, and gelling properties, preserving native functionality. These findings provide sustainable solutions for gluten-free baking and plant protein enrichment, supporting the development of high-quality, nutritionally enriched food ingredients to meet growing consumer and industry demands.
Keywords: Sorghum; Lentils; Peas; Roller milling; Dry fractionation; Gluten free